Low-cost portable dielectric spectrometer based on mini-vector network analyzer and open-ended coaxial probe technology - Zhu, Zhuzhuo; Zhu, Xinhua; Guo, Wenchuan (International Journal of Agricultural and Biological Engineering, 2024)
As a simple, fast, and non-destructive measuring technology, dielectric spectroscopy is usually used to analyze the dielectric properties of agricultural products and food, and then to predict the main components of materials. However, the large and expensive vector network analyzers (VNA) with expensive analysis software applied in measuring dielectric properties make research limited to the laboratory. To acquire dielectric spectra in situ, a model for solving relative complex permittivity was derived, and its performance was validated. Then, a low-cost portable dielectric spectrometer with a mini VNA, a Raspberry Pi, and a coaxial probe as core parts was developed over the frequency range of 100-3000 MHz. The stability and accuracy of the developed spectrometer were tested using milk and juice. The results indicated that the relative errors of the model were within ±5% for dielectric constant (ε′) and loss factor (ε′′). The coefficients of variation of measured ε′ and ε′′ by the developed spectrometer at 100-3000 MHz were less than 1% and 2%, respectively. Compared with the dielectric properties obtained by using a commercial dielectric measurement system, the relative errors of measured ε′ and ε′′ were within ±3.4% and ±6.0%, respectively. This study makes fast, non-destructive, and on-site food quality detection using dielectric spectra possible. Keywords: coaxial probe, mini vector network analyzer, low-cost, portable, dielectric spectrometerDOI: 10.25165/j.ijabe.20241703.7170Citation: Zhu Z Z, Zhu X H, Guo W C. Low-cost portable dielectric spectrometer based on mini-vector network analyzer and open-ended coaxial probe technology. Int J Agric & Biol Eng, 2024; 17(3): 166-172.